2017
DOI: 10.1155/2017/5920714
|View full text |Cite
|
Sign up to set email alerts
|

Osseointegration of a 3D Printed Stemmed Titanium Dental Implant: A Pilot Study

Abstract: In this pilot study, a 3D printed Grade V titanium dental implant with a novel dual-stemmed design was investigated for its biocompatibility in vivo. Both dual-stemmed (n = 12) and conventional stainless steel conical (n = 4) implants were inserted into the tibial metaphysis of New Zealand white rabbits for 3 and 12 weeks and then retrieved with the surrounding bone, fixed, dehydrated, and embedded into epoxy resin. The implants were analyzed using correlative histology, microcomputed tomography, scanning elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The customization of implants in the patient anatomy is associated with the development of the numeric image techniques and such three-dimensional (3D) printing technology as selective laser sintering (SLS) and selective laser melting (SLM). Both above-mentioned techniques allow for the formation of three-dimensional metal structures by selective melting of metal powder in a layer-by-layer manner, which enable the formation of products with new chemical properties, differing from their macroscopic equivalents [5,6,7]. The response of the tissues to the implant is largely controlled by the implant surface morphology and properties.…”
Section: Introductionmentioning
confidence: 99%
“…The customization of implants in the patient anatomy is associated with the development of the numeric image techniques and such three-dimensional (3D) printing technology as selective laser sintering (SLS) and selective laser melting (SLM). Both above-mentioned techniques allow for the formation of three-dimensional metal structures by selective melting of metal powder in a layer-by-layer manner, which enable the formation of products with new chemical properties, differing from their macroscopic equivalents [5,6,7]. The response of the tissues to the implant is largely controlled by the implant surface morphology and properties.…”
Section: Introductionmentioning
confidence: 99%
“…The premise was that the method should be tunable, offering the possibility of attaching different moieties according to specific needs, and should also be stable in order to resist the harsh conditions of the in vivo environment, particularly in the oral cavity. We opted for Ti 6 Al 4 V ELI alloy because it is widely used in the dental implant industry [36], and chose 3D-printed Ti 6 Al 4 V ELI pieces because metal 3D printing techniques are opening the field of implantology to increasingly improved designs in order to tackle the biomechanical issue [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Osman et al (2017) previously reported that 3D printed zirconia implants produced with digital processing technique (DLP) have good dimensional accuracy and mechanical properties similar to those of the conventionally produced ceramic implants [ 64 ]. Tedesco et al (2017) compared 3D printed implants’ biocompatibility post-insertion in the tibial metaphysis of rabbits [ 159 ]. It was reported in their study that 3D printed implants demonstrated profitable bone growth and acceptable biocompatibility [ 159 ].…”
Section: 3d Printing In Dental Implantologymentioning
confidence: 99%
“…Tedesco et al (2017) compared 3D printed implants’ biocompatibility post-insertion in the tibial metaphysis of rabbits [ 159 ]. It was reported in their study that 3D printed implants demonstrated profitable bone growth and acceptable biocompatibility [ 159 ]. Chang et al (2020) used 3D printed Bio-Active ITRI dental implants (produced via laser-sintered 3D printing method) in the femur of white rabbits to analyze their performance in a large bone defect area [ 164 ].…”
Section: 3d Printing In Dental Implantologymentioning
confidence: 99%